Answer:
10
Step-by-step explanation:
20 divided by 4 = 5 and times it from there
D/13>-3
You have to multiply 13 in both sides to eliminate the Denominator 13 on the left leaving variable D only.
(D/13)(13) > -3(13)
D > -39
so... D. D > -39
Answer: equation of the tangent plane is z = 1
Step-by-step explanation:
Given equation
z = e^(-x²-y²) at point (0,0,1)
now let z = f(x,y)
Δf(x,y) = [ fx, fy ]
= (-2xe^(-x²-y²)), (-2ye^(-x²-y²))
now
Δf (0,0) = [ 0, 0 ] = [ a, b ]
equation of the tangent plane therefore will be
z - z₀ = a(x-x₀) + b(y-y₀)
z - 1 = 0(x-0) + 0(y-0)
z - 1 = 0 + 0
z = 1
Therefore equation of the tangent plane is z = 1
Answer:
x = 2
Step-by-step explanation:
these angles are alternate-interior angles which are congruent
-1 + 38x = 36x + 3
38x = 36x + 4
2x = 4
x = 2